The Belief Stories in the Texts of Oral History of the People in Late Adulthood Period - Gocół, Damian (Vilnius University Open Series, 2021)
In my article, I analyze selected belief stories from the oral history texts. The research material contains the three biographical accounts of the people in late adulthood (over 65). The belief stories (belief tales) are one of the genres of speech typical for the accounts rooted in a folk view of the world. The demonic characters appear in them, e. g. the devil, the striga or the południca. The belief stories contain a detailed description of the world. They have an explanatory function. They are to explain how the world works. Belief stories do not appear often in the oral history texts created by the people in late adulthood who were not related to the countryside or were related to it in a limited extent. This way of shaping the narrative may be related to changes in the rationality of the narrators. The common and the scientific view of the world intersect in their narratives. The narrators add the numerous comments to their belief stories, in which they distance themselves from the folk view of the world or try to scientifically rationalize the fantastic events. Nevertheless, the fragments in which other genres of speech are realized, especially in anecdotes, reveal a clear relationship between the narrative of oral history and the common sense and belief vision of the world. The narrators often explain their own experiences by introducing elements of belief tales into other genres. Such fragments reveal the schemes of punishment and reward, non-worldly divine intervention, anthropomorphization of inanimate objects and assigning them the rank of demonic beings. Despite the intersection of different types of rationality in the narratives, a belief-based vision of the world still plays an important role in shaping of the oral narratives about the past.
Keywords: oral history; memory; legend; anecdote; common rationality